Bridging the divide: the adjustment and decision-making experiences of people with dementia living with a recent diagnosis of cancer and its impact on family carers. Issue 5 (25th May 2020) - McWilliams, Lorna; Swarbrick, Caroline; Yorke, Janelle; Burgess, Lorraine; Farrell, Carole; Grande, Gunn; Bellhouse, Sarah; Keady, John
Abstract: The risk of living with dementia and, separately, cancer, increases exponentially with age. However, to date, there is a paucity of research investigating the experiences of people living with both these conditions. This study used semi-structured interviews to explore the decision-making and treatment options for people who live with both dementia and cancer. In total, ten people living with both dementia and cancer (aged 39–93 years) and nine family carers were interviewed. Braun and Clarke's approach to thematic analysis was used together with framework matrices to organise the data. In this article four sequential and descriptive themes are presented. 'Reaching a diagnosis of cancer' describes the vital role that family carers play in encouraging the person with dementia to seek an explanation for their presenting (undiagnosed cancer) symptoms to their general practitioner. 'Adjusting to the cancer diagnosis when living with dementia' outlines a variety of emotional and practical responses to receiving news of the diagnosis. 'Weighing up the cancer treatment options' highlights the different decisions and circumstances that family carers and people living with both dementia and cancer are faced with post-diagnosis. 'Undergoing cancer treatment' shares the finding that cancer treatment decision-making was not straightforward and that people living with both dementia and cancer would often forget about their cancer and what procedures they had been through.